Sebaran Daun Sang (Johannesteijsmannia altifrons) Berdasarkan Kelerengan dan Ketinggian Tempat / Distribution of Daun Sang (Johannesteijsmannia altifrons) Based on Slope and Altitude of Place - Siti Harianti Manurung; Siti Latifah; Kansih Sri Hartini (Program studi Kehutanan USU, 2013)
Daun Sang is an plant endemic of Sumatera. This plant only found in two places in Indonesia in Bukit Tigapuluh National Park and Gunung Leuser National Park. This research is important to rescue Daun Sang. Based on spatial analysis can provide important and accurate information about the habitat linkages of Daun Sang. Daun Sang of the components of a particular habitat, areas that may be used as habitat for Daun Sang, or they can be for the predict Daun Sang population in an area and view information about the condition of habitat at any given time. This study aims to map the distribution of Daun Sang and predict the level of habitat suitability based on altitude. Belt Transect used for this research and overlap (overlay) to create a map of the distribution of Daun Sang. The results showed that Daun Sang were found scattered near each other between one individual with another individual on sloping land and grow in the shade of the trees. Daun Sang habitat suitability for altitude in the resort level Sei Betung is ≥ 60 masl and high suitability for level terrain is